Sexual Dimorphism in Hematocrit Response Following Red Blood Cell Transfusion of Critically Ill Surgical Patients. (22nd March 2012) - Pieracci, Fredric M.; Barnett, Carlton C.; Townsend, Nicole; Moore, Ernest E.; Johnson, Jeffery; Biffl, Walter; Bensard, Denis D.; Burlew, Clay C.; Gerber, Andrew; Silliman, Christopher C.
Abstract : The change in hematocrit (ΔHct) following packed red blood cell (pRBCs) transfusion is a clinically relevant measurement of transfusion efficacy that is influenced by post-transfusion hemolysis. Sexual dimorphism has been observed in critical illness and may be related to gender-specific differences in immune response. We investigated the relationship between both donor and recipient gender and ΔHct in an analysis of all pRBCs transfusions in our surgical intensive care unit (2006–2009). The relationship between both donor and recipient gender and ΔHct (% points) was assessed using both univariate and multivariable analysis. A total of 575 units of pRBCs were given to 342 patients; 289 (49.9%) donors were male. By univariate analysis, ΔHct was significantly greater for female as compared to male recipients (3.81% versus 2.82%, resp., P < 0.01 ). No association was observed between donor gender and ΔHct, which was 3.02% following receipt of female blood versus 3.23% following receipt of male blood (P = 0.21 ). By multivariable analysis, recipient gender remained associated significantly with ΔHct (P < 0.01 ). In conclusion, recipient gender is independently associated with ΔHct following pRBCs transfusion. This association does not appear related to either demographic or anthropomorphic factors, raising the possibility of gender-related differences in recipient immune response to transfusion.